PELATIHAN PENJUALAN ONLINE MENGGUNAKAN MARKETPLACE PADA UKM DI BANTUL - Keny Rahmawati (Dharma: Jurnal Pengabdian Masyarakat, 2021)
At this time, information technology, especially the internet, has increased very rapidly. The increasing user of the interney in Indonesia has affected the development of e-commerce in Indonesia, especially the marketplace. One of the biggest marketplace player in Indonesia is Shopee. Based on data obtained form the Department of Cooperatives, MSMEs, and Industry of Bantul, currently there are 141 thousand MSMEs players who are covered by 351 cooperatives in Bantul. One of them is AMBOY (Agro Mirasa Boga Bantul Yogyakarta). The internet is used to help market business ventures through online sales by some cooperative members. However, some of members still sell in the traditional way. The constraint experienced by cooperative members is a lack of literacy regarding the use of the internet. Online sales training using marketplace is the right choice to overcome the obstacles faced by AMBOY Members. In this training, members of AMBOY will be taught how to sell their products in the marketplace in order to develop and expand their market.